Differentiation of Out-of-Pocket Expenditures in Cancer Patients; A Case Study in the Cancer Institute of Iran - Aboghasem Pourreza; Iraj Harirchi; Mohammad Bazyar (Shahid Sadoughi University of Medical Sciences, 2017)
Background: The Cancer Institute of Iran, located in Tehran (Iran’s capital city), is a national specialized center for cancer. Cancer patients from all over the country refer to it. This study compared the out-of-pocket  (OOP)  expenditures of patients from Tehran and patients from other parts of Iran who were hospitalized in this center. Methods: This cross-sectional study included all patients over 18 years of age with head and neck or digestive system cancer who were actively undergoing primary treatment in the Cancer Institute of Iran located in Tehran (the capital city). Data was collected through a structured interview with the patients themselves and/or their companions and then analyzed using SPSS16 software. Results: Direct medical costs of patients from Tehran were much higher than those of patients from other provinces. In contrast, the average direct non-medical costs including transportation, accommodation, food, etc. of patients from other provinces were significantly higher than those of patients from Tehran, and 53% of patients borrowed money for their treatments. Conclusion: It seems necessary to develop new supportive policies to alleviate financial costs for cancer patients and help them manage their cancers effectively. Patients from the provinces faced additional costs for travel, food, and accommodations which complicated their access to special services. Establishing and improving specialized cancer centers in other cities can reduce the burden of out-of-pocket expenditures for patients from remote areas.